Analisis Pengendalian Persediaan Bahan Baku Menggunakan Metode Probabilistik Model P (Back Order) untuk Meminimalkan Biaya Persediaan pada UD XYZ - Akbar Ramadhani; Sajiyo Sajiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
An adequate supply of raw materials is one of the main factors in maintaining the smooth operation of the production process in the manufacturing industry. UD XYZ , a company that produces shoe soles, has experienced a shortage of raw materials, which has affected the production process and hindered the achievement of production targets. The purpose of this study is to analyze the inventory control system and determine the most efficient inventory policy. The methods used include forecasting with Moving Average (MA), Weighted Moving Average (WMA), and Single Exponential Smoothing (SES), as well as inventory control with the probabilistic P-Back Order Model. The results of the study show that the most optimal inventory solution is obtained in the fourth iteration with an order interval of 0.0891 years, an order quantity of 3,991.06 kg, a safety stock of 659.09 kg, a reorder point of 4,650.15 kg, and a total inventory cost of Rp 1,527,552,249.94. Implementing this policy is expected to minimize the risk of shortage, increase inventory efficiency, and support the smooth operation of the company's production activities.